2020
DOI: 10.1109/access.2020.3007499
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Machine Learning Algorithm Using Fine-Grained-Mode Spark on a Mesos Big Data Cloud Computing Software Framework for Mobile Robotic Intelligent Fault Recognition

Abstract: An accurate and efficient intelligent fault diagnosis of mobile robotic roller bearings can significantly enhance the reliability and safety of mechanical systems. To improve the efficiency of intelligent fault classification of mobile robotic roller bearings, this paper proposes a parallel machine learning algorithm using fine-grained-mode Spark on a Mesos big data cloud computing software framework. Through the segmentation of datasets and the support of a parallel framework, the parallel processing technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Another thrilling revelation is that most studies [70,77,79,84,94,97,106,108,[116][117][118][119][120][121] used Deep Neural Networks (DNN), such as LSTM and Convolutional Neural Network (CNN), as shown in Fig. 6.…”
Section: Big Data Platforms Tool In Bdamentioning
confidence: 99%
See 1 more Smart Citation
“…Another thrilling revelation is that most studies [70,77,79,84,94,97,106,108,[116][117][118][119][120][121] used Deep Neural Networks (DNN), such as LSTM and Convolutional Neural Network (CNN), as shown in Fig. 6.…”
Section: Big Data Platforms Tool In Bdamentioning
confidence: 99%
“…We observed that several studies [70,83,85,87,88,92,95,97,104,108,117,119,122,124,125] combined two or more metrics to evaluate their models and framework.…”
Section: Evaluation Metrics Used In Bdamentioning
confidence: 99%
“…Bearing fault diagnosis method is based on inner product continuation local mean decomposition and support vector machine (SVM) [12]. Online fault analysis method is based on improved multi-scale fuzzy entropy [13], while intelligent fault identification is based on relatively big data software and parallel machine learning algorithms [14]. Another example of diagnosis method is the fault diagnosis method founded on noise reduction technology and improved convolutional neural network (CNN) [15].…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of big data technology, many scholars have carried out extensive research on fault diagnosis in industrial big data scenarios [19], [20], [21], [22], [23], [24], [25]. For example, some studies combine big data technology and data-driven fault diagnosis methods to diagnose faults of mobile robot [21], sulfur hexafluoride electrical equipment [22], power grid equipment [23], wind turbine gearbox [24], and reciprocating air compressor [25]. Most of the above-mentioned studies use MapReduce [26] or Spark [27] to parallelize the fault diagnosis models to improve the performance of industrial equipment fault diagnosis in the big data environment.…”
Section: Introductionmentioning
confidence: 99%